Epigenetics of the myotonic dystrophy-associated DMPK gene neighborhood. (January 2016) - Buckley, Lauren; Lacey, Michelle; Ehrlich, Melanie
Aim: Identify epigenetic marks in the vicinity of DMPK (linked to myotonic dystrophy, DM1) that help explain tissue-specific differences in its expression.Materials & methods: At DMPK and its flanking genes ( DMWD, SIX5, BHMG1 and RSPH6A ), we analyzed many epigenetic and transcription profiles from myoblasts, myotubes, skeletal muscle, heart and 30 nonmuscle samples.Results: In the DMPK gene neighborhood, muscle-associated DNA hypermethylation and hypomethylation, enhancer chromatin, and CTCF binding were seen. Myogenic DMPK hypermethylation correlated with high expression and decreased alternative promoter usage. Testis/sperm hypomethylation of BHMG1 and RSPH6A was associated with testis-specific expression. G-quadruplex (G4) motifs and sperm-specific hypomethylation were found near the DM1-linked CTG repeats within DMPK .Conclusion: Tissue-specific epigenetic features in DMPK and neighboring genes help regulate its expression. G4 motifs in DMPK DNA and RNA might contribute to DM1 pathology.